2010
DOI: 10.2174/1874291201004020025
|View full text |Cite
|
Sign up to set email alerts
|

Urban Living is Not Associated with Better Birth and Infant Outcomes among Inuit and First Nations in Quebec~!2009-11-30~!2010-04-12~!2010-07-06~!

Abstract: ObjectiveThere is limited and inconsistent evidence concerning rural versus urban differences in birth and infant outcomes for Indigenous peoples. We assessed birth and infant outcomes among Inuit, First Nations and French mother tongue groups by rural versus urban residence in Quebec, Canada.Study DeignA retrospective birth cohort study of 5,184 First Nations, 2,527 Inuit and 652,940 French mother tongue (the majority reference) births in Quebec, 1991–2000.ResultsIn general, rural living was associated with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“… 16 However, this effect has not been unequivocally demonstrated for maternal and infant mortality or adult mortality in Canada and Australia. 25 , 26 The gradient of worsening outcomes with increasing rurality/remoteness is an additional finding not previously reported in the New Zealand literature. Studies have identified similar mortality gradients with increasing rurality in Australia and the US, 27 , 28 although the Australian evidence for such an effect is conflicting.…”
Section: Discussionmentioning
confidence: 69%
“… 16 However, this effect has not been unequivocally demonstrated for maternal and infant mortality or adult mortality in Canada and Australia. 25 , 26 The gradient of worsening outcomes with increasing rurality/remoteness is an additional finding not previously reported in the New Zealand literature. Studies have identified similar mortality gradients with increasing rurality in Australia and the US, 27 , 28 although the Australian evidence for such an effect is conflicting.…”
Section: Discussionmentioning
confidence: 69%
“…Though the underlying causes are indistinguishable, socioeconomic status, poor community and social support, and lack of access to traditional healthy diets can be among the contributing factors. 24 This study is joining many recent studies that have revealed that despite the overall health improvement across the country, racial and ethnic minorities still receive a lower quality of health care than nonminorities. The authors strongly believe that a sincere effort and holistic approach should be adopted by all stakeholders on different levels to manage this problem.…”
Section: Discussionmentioning
confidence: 89%
“…This finding is consistent with several previous studies demonstrating greater urban disparities in birth outcomes in some regions of the United States and Canada. [24][25][26][27] The proposed rationales for the racial disparities include, first, the socioeconomic status of the patients' families, where the economically disadvantaged parents cannot afford healthrelated expenses, 28,29 and, second, the geographic distance of the patient's families from health care facilities, which can be an economic burden and cause delays in or an inability to receive the required medical/surgical care for their children. 30 It is counterintuitive that living in urban areas close to the health care facilities did not result in better survival outcomes for gastroschisis patients.…”
Section: Discussionmentioning
confidence: 99%
“…A growing number of Aboriginal peoples, especially the young, live in urban areas. Simonet and colleagues assess whether living in urban areas is associated with better birth and infant outcomes among Canadian First Nations and Inuit in Quebec [3]. The findings are somewhat discouraging.…”
Section: Editorial What We Have Known About Community Characteristicsmentioning
confidence: 99%